New Onset On-Medication Freezing of Gait After STN-DBS in Parkinson's Disease - Mei, Shanshan; Li, Jiping; Middlebrooks, Erik H.; Almeida, Leonardo; Hu, Wei; Zhang, Yuqing; Ramirez-Zamora, Adolfo; Chan, Piu (Frontiers in Neurology, 2019)
Freezing of gait (FoG) is commonly observed in advanced Parkinson's disease (PD) and it is associated with reduced mobility, recurrent falls, injuries, and loss of independence. This phenomenon typically occurs as the effect of dopaminergic medications wears off (“off” FoG) but on rare occasions, it can also be observed during peak medication effect (“on” FoG). In this report, we present the case of a 65-year-old female with a 13-year history of akinetic-rigid idiopathic PD who developed recurrent episodes of “on” FoG after bilateral subthalamic nucleus deep brain stimulation (STN-DBS). She underwent STN-DBS for management of motor fluctuations, which resulted in a marked improvement in her motor symptoms. Within the next 6 months and after several programming sessions, the patient reported “on” FoG occurring regularly 1 h after taking levodopa and lasting a few hours. Accordingly, a repeated levodopa challenge showed that FoG resolved with either levodopa administration or STN stimulation alone, but the combination of both therapies induced recurrence of FoG in our patient. Subsequent management was complex requiring adjustments in levodopa dose and formulation along with advanced DBS programming.